Making the Standard of Audiovisual Text for the Deaf and Hearing Impaired - Alvin Taufik (Journal of English Language and Culture, 2018)
The development of television and film industry in a global context requires film and television industry to be able to present the shows that can be enjoyed by the general public without any restrictions. This phenomenon essentially underlies the emergence of community needs for audiovisual translation (layman terms: the subtitle). The industrialized world utilize audioviual translation in order to visualize verbal messages in other languages so that it can be understood. However, any progress in the field of audiovisual is not coupled with accessibility for all individuals. Providers of text or audio in existing programs, so far, have not fully considered deaf people or those with hearing impaired (deaf or hearing impaired/DH). In line with that, a set of standard is required to meet the needs of the DH. Referring to the high demand for audiovisual translation and the view on the audiovisual translation which has not yet met the needs of the DH, This research is fundamentally directed to create audiovisual translation standards which is appropriate for all audiences specifically for the DH. This study is a qualitative study using library research approach. Therefore, the analysis is directed at the analysis of the current product and its shortcomings. To be able to meet the demand for audiovisual translation standards, researchers will undertake a number of steps that includes product analysis research and product development. This study is expected to be the basis for making an audiovisual translation quality products which can be enjoyed by all audiences.Keywords: Audiovisual translation, deaf or hearing impaired, research and development